Design and optimization of HTS flux-switching permanent magnet machine - Shuraiji, Ahlam Luaibi; Al-ani, M.M.J. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Flux-switching permanent magnet (FSPM) machine with high temperature superconductors (HTS) bulks located between the rotor poles to eliminate the flux leakage in the rotor, termed as (HTS-FSPM) machine has been proposed in this paper. Using genetic algorithm, the HTS and the conventional FSPM machines having the same size constraints and load conditions have been globally optimized for max. aveage torque. To highlight the advantages of the HTS-FSPM machine, a performance comparison between the conventional and HTS-FSPM machines has been presented. It is found that the HTS-FSPM machine can increase the torque by 27%, however, this comes with the expense of higher torque ripple and power losses.